LISTENING TO THE ELDER BROTHERS: ANIMALS, AGENTS, AND POSTHUMANISM IN NATIVE VERSUS NON-NATIVE AMERICAN MYTHS AND WORLDVIEWS. - Thompson, Tok (Folklore (14060957), 2019)
Contrasting with much of Western discourse, Native American myths frequently ascribe world-creating deeds to non-human animals. Further, Native American stories display a remarkable slippage between the worlds of the human and non-human animals, a slippage that continues into worldview, rituals, and everyday life. Using these stories as a starting point, this article seeks to connect the current theoretical movements in posthumanism with those in mythology, in line with Graham Harvey's call for "academic animism", a re-appraisal of the role of non-human agency and culture. New developments in animal studies have revolutionized the way scholars perceive of non-hominid mental lives and abilities, which has led to challenges to traditional Western beliefs and practices. Many of these new concepts would be old news to Native Americans, whose traditions fundamentally and categorically posit radically different relationships than the non-native. In short, this paper will present a mytho-evolutionary blueprint for broadening our understanding of culture and narrative far beyond the human, yet including the human as well, as part and parcel of cultural life on earth.